Pelatihan Sablon Totebag Menggunakan Kertas Nasi bagi Siswa SMP Negeri 3 Galang sebagai Upaya Peningkatan Keterampilan Wirausaha Muda - Nia Widia Tarihoran; Cindy Fatika Dwi; Khairunnisa Harahap; Khairana Tantri; Sri Rahma Yani Harahap (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
One skill that has economic potential and is relatively easy to learn is tote bag screen printing using simple materials such as rice paper. This community service program aims to enhance the entrepreneurial skills of students at SMP Negeri 3 Galang through tote bag screen printing training using rice paper. The training was conducted using a hands-on method and a participatory approach. The stages of the activity included preparation, material introduction, business opportunity discussions, screen printing practice, and evaluation of student products. The results showed a significant improvement in students’ technical knowledge and skills, the growth of creativity in tote bag design, and an emerging interest in turning this skill into a business opportunity. The school’s response to this program was very positive, encouraging the continuation of similar initiatives. Challenges encountered included the relatively long drying time of the glue and limited tools and materials. Overall, this training not only produced tote bags with economic value but also to the development of students’ independence, creativity, and entrepreneurial spirit from an early age.